Transparent microcrystalline glass as well as preparation method and application thereof

By preparing transparent microcrystalline glass, the problems of stability and luminous performance of solid-state luminescent materials in high-temperature environments are solved, and efficient application of luminescent materials is achieved, suitable for display and high-power lighting fields.

CN119118515AActive Publication Date: 2024-12-13WUYI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411106068.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-13
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Existing solid-state luminescent materials are prone to problems such as decreasing luminescence efficiency, aging of organic resins and color development drift in long-term high-temperature environments, resulting in poor stability and luminescence performance of lighting devices.

Method used

Using transparent microcrystalline glass, a phase-changeable α-Sr2SiO4:Eu2+, β-Sr2SiO4:Eu2+ single or double crystal phase with spotted crystal morphology is prepared by specific components at heating and melting temperature, as a completely inorganic fluorescent material. Replace the fluorescent film mixed with traditional organic resin and phosphor to improve radiation resistance and thermal stability.

Benefits of technology

It achieves retention of more than 70% of the luminous intensity at 150°C and has a quantum efficiency of more than 74%. It is suitable for display and high-power lighting fields, extending the service life of lighting devices and improving the luminous performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118515A_ABST
    Figure CN119118515A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid luminescent materials, and discloses transparent microcrystalline glass as well as a preparation method and application thereof. The transparent microcrystalline glass comprises alpha-Sr2SiO4: Eu < 2 + > single crystal phase transparent microcrystalline glass, beta-Sr2SiO4: Eu < 2 + > single crystal phase transparent microcrystalline glass, or at least one of alpha-Sr2SiO4: Eu < 2 + > and beta-Sr2SiO4: Eu < 2 + > double crystal phases. The transparent microcrystalline glass has excellent stability and luminescent property, can be widely applied to the field of display or illumination, and is particularly suitable for the field of outdoor display and high-power illumination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid luminescent materials, and in particular relates to a transparent microcrystalline glass and a preparation method and application thereof. Background Art

[0002] Solid-state lighting technology is developing towards higher brightness, lower power consumption, smaller size and lower cost. White light emitting diodes (WLED) and white laser diodes (WLD) have attracted widespread attention in the market in recent years due to their high efficiency, high brightness, long life and environmental protection.

[0003] At present, there are generally three solutions to achieve white light sources. The first solution is to combine three separate monochromatic LED / LD (light-emitting diode / laser diode) chips to emit red, green and blue light to obtain white light. This method has a wide color gamut and high luminous efficiency. The second solution is to combine the blue LED / LD chip with yttrium aluminum garnet YAG:Ce 3+ WLED / WLD made of yellow phosphor has occupied more than half of the white light lighting market due to its high luminous efficiency and low cost. The third solution is to combine 365nm ultraviolet LED / LD chip with red, green and blue phosphors excited by ultraviolet band. The advantage of WLED realized in this way is good color uniformity and high color rendering.

[0004] Due to the high cost of chips, the solution of combining red, green and blue chips to obtain white light is not recognized by the public, so the most widely used WLED / WLD on the market is mainly made by using LED / LD chips as the substrate and adding corresponding phosphors. Generally speaking, white light sources are generally obtained by irradiating LED / LD chips on phosphors that are fully mixed with organic resins for light conversion. Under such long-term irradiation in high-temperature environments, phosphors will face problems such as thermal quenching and decreased luminous efficiency. In addition, long-term irradiation will also accelerate the aging and yellowing of organic resins, and even ablation, which will bring serious problems such as color drift and lighting devices not being able to work properly. In addition, the luminescence performance and stability (such as thermal stability) of existing solid-state luminescent materials also need to be further improved.

[0005] Therefore, in order to solve the above problems, there is an urgent need for an all-inorganic solid luminescent material with excellent optical properties that does not require auxiliary packaging using organic resins and also has good luminescent properties and stability. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a transparent microcrystalline glass and a preparation method and application thereof. The transparent microcrystalline glass of the present invention is a kind of all-inorganic fluorescent transparent microcrystalline glass, which has excellent stability and luminescence performance. The transparent microcrystalline glass of the present invention is used to replace the traditional fluorescent film mixed with organic resin and phosphor covering the LED / LD chip, which can effectively prevent the decline of luminous efficiency and the aging, yellowing and carbonization of the organic resin. Therefore, the WLED / WLD device prepared by coupling the LED / LD chip with the transparent microcrystalline glass having good radiation resistance, excellent luminous efficiency and thermal stability and low manufacturing cost of the present invention will have the advantages of longer service life and excellent luminescence performance, and can be widely used in the display or lighting fields, especially suitable for outdoor display and high-power lighting fields.

[0007] The transparent microcrystalline glass of the present invention is prepared by controlling the crystallization of specific component raw materials at a specific heating melting temperature to obtain a fluorescent α-Sr2SiO4:Eu with a spot-like crystal morphology that can be phase-changed. 2+ Single crystal phase transparent glass-ceramics, β-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, and α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Dual-crystal phase transparent microcrystalline glass. The transparent microcrystalline glass has excellent stability (still retains more than 70% of the initial luminous intensity at 150°C) and excellent luminous performance (quantum efficiency exceeds 74%), and can be widely used in display or lighting fields, especially suitable for outdoor display and high-power lighting fields.

[0008] A first aspect of the present invention provides a transparent glass-ceramic.

[0009] Specifically, a transparent microcrystalline glass includes α-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, β-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, or α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ At least one of the twin crystal phases.

[0010] Preferably, the α-Sr2SiO4:Eu 2+ The single crystal phase has a spot-like crystal morphology.

[0011] Preferably, the β-Sr2SiO4:Eu 2+ The single crystal phase has a spot-like crystal morphology.

[0012] Preferably, the α-Sr2SiO4:Eu2+ and β-Sr2SiO4:Eu 2+ The twin crystal phase has a spotty crystal morphology.

[0013] Preferably, the α-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, β-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ The grain length of the twin crystal phase is 1-12 μm, more preferably 2-10 μm.

[0014] Preferably, the transparent glass-ceramics can emit a strong broadband spectrum in the 400 to 700 nm band under 365 nm light excitation, and further the main emission peak is located at 532 nm.

[0015] Preferably, the quantum efficiency of the transparent glass-ceramics is not less than 74%, for example, 75-85%.

[0016] Preferably, the transparent microcrystalline glass still retains more than 70% of the initial luminous intensity at 150° C. For example, the luminous intensity retains 70-85% of the initial luminous intensity.

[0017] A second aspect of the present invention provides a method for preparing transparent microcrystalline glass.

[0018] Specifically, a method for preparing transparent microcrystalline glass comprises the following steps:

[0019] Weighing SiO2, SrO, and Eu2O3 raw materials, then mixing them, heating and melting them in a reducing atmosphere, and then cooling them to obtain the transparent microcrystalline glass;

[0020] In the raw material, the molar percentage of SiO2 is 40-60%, the molar percentage of SrO is 40-60%, and the molar percentage of SrO is greater than the molar percentage of SiO2;

[0021] The heating and melting temperature exceeds 1510°C.

[0022] Preferably, in the raw material, the molar percentage of Eu2O3 is 0.01-2%, and more preferably 0.1-0.5%.

[0023] Preferably, in the raw material, the molar percentage of SiO2 is 40-60%, the molar percentage of SrO is 40-60%, the molar percentage of Eu2O3 is 0.01-2%, and the molar percentage of SrO is greater than the molar percentage of SiO2.

[0024] Further preferably, in the raw material, the molar percentage of SiO2 is 45%, the molar percentage of SrO is 54.9%, and the molar percentage of Eu2O3 is 0.1%.

[0025] Preferably, the heating and melting temperature is 1570-1640°C, more preferably 1580-1600°C.

[0026] Preferably, the heating and melting temperature is maintained at 1570-1640° C. for 0.8-6 hours, more preferably for 1-2 hours.

[0027] Preferably, the reducing atmosphere is selected from at least one of H2, CO or carbon powder.

[0028] Preferably, the mixing process is carried out by grinding, for example, grinding for 20-30 minutes.

[0029] Preferably, the cooling is natural cooling to room temperature, for example, cooling to room temperature in a muffle furnace.

[0030] Preferably, the cooling time is 6-12 hours, more preferably 8-10 hours.

[0031] A third aspect of the present invention provides an application of a transparent microcrystalline glass.

[0032] A display or lighting device comprises the transparent microcrystalline glass.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) The present invention adopts specific preparation conditions (raw material ratio and heating melting temperature) to prepare transparent fluorescent α-Sr2SiO4:Eu with spot-like crystal morphology. 2+ Single crystal phase transparent glass-ceramics, β-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics, or α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ The double crystal phase transparent microcrystalline glass has a hard, dense and uniform texture and has stable physical and chemical properties. The transparent microcrystalline glass has excellent stability (still retains more than 70% of the initial luminous intensity at 150°C) and excellent luminous performance (quantum efficiency exceeds 74%), and can be widely used in display or lighting fields, especially suitable for outdoor display and high-power lighting fields.

[0035] (2) α-Sr2SiO4:Eu under ultraviolet light excitation 2+ Single crystal phase transparent glass-ceramics, α-Sr2SiO4:Eu 2+Single crystal phase and β-Sr2SiO4:Eu 2+ The double crystal phase transparent glass-ceramics can emit strong green light (quantum efficiency reaches 75%), β-Sr2SiO4:Eu 2+ Single crystal phase transparent glass-ceramics can emit yellow-green light.

[0036] (3) The present invention prepares a phase-changeable transparent fluorescent microcrystalline glass containing a spot-like crystal morphology. The crystal phase in the microcrystalline glass can be changed from α-Sr2SiO4:Eu 2+ Single-phase modulation α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Twin phase, then β-Sr2SiO4:Eu 2+ Single phase.

[0037] (4) The transparent microcrystalline glass of the present invention is prepared in a one-step process, which has simple process, low cost, non-toxicity and pollution-free. The transparent microcrystalline glass material has excellent luminescence performance and can be developed as a green broadband fluorescent solid luminescent material and applied in solid-state lighting. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the XRD diagram of the precursor amorphous glass of Comparative Example 1 of the present invention;

[0039] Figure 2 This is a digital photo of the precursor amorphous glass of Comparative Example 1 of the present invention;

[0040] Figure 3 The normalized excitation and emission spectra of the precursor amorphous glass of Comparative Example 1 of the present invention;

[0041] Figure 4 This is the XRD diagram of the transparent glass-ceramics of Example 1 of the present invention;

[0042] Figure 5 This is a digital photo of the transparent glass-ceramics of Example 1 of the present invention;

[0043] Figure 6 This is a morphology image taken by a scanning electron microscope (SEM) of the transparent glass-ceramics in Example 1 of the present invention;

[0044] Figure 7 This is a normalized excitation and emission spectrum diagram of the transparent glass-ceramics of Example 1 of the present invention;

[0045] Figure 8 This is a morphology image taken by a scanning electron microscope (SEM) of the transparent glass-ceramics of Example 2 of the present invention;

[0046] Fig. 9 Graphs showing normalized excitation and emission spectra of the transparent glass-ceramics of Example 2 of the present invention;

[0047] Fig.10 This is a temperature-varying spectrum diagram of the transparent glass-ceramics of Example 2 of the present invention;

[0048] Fig.11 This is a normalized excitation and emission spectrum diagram of the transparent glass-ceramics of Example 3 of the present invention;

[0049] Fig.12 This is a morphology image taken by a scanning electron microscope (SEM) of the transparent glass-ceramics of Example 4 of the present invention;

[0050] Fig.13 This is a normalized excitation and emission spectrum diagram of the transparent microcrystalline glass according to Example 4 of the present invention.

[0051] Fig.14 This is the XRD diagram of the amorphous glass of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0052] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0053] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0054] Figure 1 , Figure 4 , Fig.14 "Intensity" means intensity, 2θ means diffraction angle, and "degree" means degree. Figure 4 The “PDF#39-1256” in the table indicates the standard card of β-Sr2SiO4, and the “PDF#38-0271” indicates the standard card of α-Sr2SiO4.

[0055] Figure 3 , Figure 7 , Fig. 9 , Fig.11 , Fig.13 "Intensity" here means intensity, and "Wavelength" means wavelength.

[0056] Fig.10 "Wavelength" means wavelength, "Temperature" means temperature, "High" means high, and "Low" means low.

[0057] Comparative Example 1

[0058] A method for preparing a precursor amorphous glass comprises the following steps:

[0059] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.9 mol% SrO, and 0.1 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0060] S2. Place the crucible with the raw materials in a large covered crucible covered with activated carbon powder as a reducing atmosphere, and keep it warm in a muffle furnace at 1600°C for 1 hour to melt it. Take it out immediately after melting, and pour the melt into a copper mold preheated at 500°C to obtain a precursor amorphous glass.

[0061] from Figure 1 It can be seen from the X-ray diffraction peaks that there is no crystal diffraction peak in the precursor amorphous glass prepared in this comparative example 1, indicating that amorphous glass is prepared.

[0062] The precursor amorphous glass prepared in this comparative example 1 still has excellent transparency when the thickness is 3 mm (see Figure 2 , you can see the word "Glass").

[0063] Under the excitation of 365nm wavelength violet light, the precursor amorphous glass prepared in this comparative example 1 exhibits bright yellow luminescence. The normalized excitation and emission spectra at room temperature are measured by Edinburgh FS980 fluorescence spectrometer. Figure 3 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 transitions, which are typically broad peak emissions, but there are also some corresponding to Eu 3+ The luminescence peak. Its luminescence center wavelength is at 588nm, the excitation spectrum covers a wide band of 250n-500nm, and the excitation peak is at 400nm.

[0064] Comparative Example 2

[0065] A method for preparing glass comprises the following steps:

[0066] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.9 mol% SrO, and 0.1 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0067] S2. Place the crucible containing the raw materials in a large covered crucible covered with activated carbon powder as a reducing atmosphere, keep it warm in a muffle furnace at 1400° C. for 1 hour, and then slowly cool it from 1400° C. to room temperature over 8 hours in the muffle furnace to obtain a product.

[0068] In this comparative example, due to the low melting temperature, bulk microcrystalline glass cannot be obtained.

[0069] Comparative Example 3

[0070] A method for preparing amorphous glass comprises the following steps:

[0071] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 70 mol% SiO2, 29.5 mol% SrO, and 0.5 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0072] S2. Place the crucible with the raw materials in a large covered crucible covered with activated carbon powder as a reducing atmosphere, keep it warm in a muffle furnace at 1600°C for 1 hour to melt it, and then slowly cool it from 1600°C to room temperature in the muffle furnace over 8 hours to obtain a block of amorphous glass.

[0073] The XRD pattern of the amorphous glass prepared in this comparative example is as follows Fig.14 As shown. Fig.14 It can be seen from the X-ray diffraction peaks that there is no crystal diffraction peak in the amorphous glass prepared in this comparative example, indicating that amorphous glass is prepared.

[0074] Example 1

[0075] A transparent microcrystalline glass comprising α-Sr2SiO4:Eu 2+ Single crystal phase.

[0076] A method for preparing transparent microcrystalline glass comprises the following steps:

[0077] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.99 mol% SrO, and 0.01 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0078] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 8 hours in the muffle furnace to obtain a block of α-Sr2SiO4:Eu 2+ Transparent glass-ceramics in single crystal phase.

[0079] from Figure 4 It can be seen from the X-ray diffraction peaks that α-Sr2SiO4:Eu 2+ Single crystal phase.

[0080] The transparent glass-ceramics prepared in this embodiment still has a certain degree of transparency when the thickness is 2 mm (see Figure 5 (a) in the figure), and further observed under a scanning electron microscope (SEM) that a microcrystalline glass with a 2-10 μm spot-like crystal morphology was successfully prepared (see Figure 6 ).

[0081] Under the excitation of 365 nm wavelength violet light, the transparent micro-ceramic glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured by Edinburgh FS980 fluorescence spectrometer. Figure 7 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 532nm. The excitation spectrum covers a wide band of 250-450nm, and the excitation peak is at 365nm.

[0082] Example 2

[0083] A transparent microcrystalline glass comprising α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Twin crystal phase.

[0084] A method for preparing transparent microcrystalline glass comprises the following steps:

[0085] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.9 mol% SrO, and 0.1 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0086] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 8 hours in the muffle furnace to obtain a block of α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Transparent glass-ceramics with twin crystal phases.

[0087] from Figure 4 It can be seen from the X-ray diffraction peaks that α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Twin crystal phase.

[0088] The transparent glass-ceramics prepared in this embodiment still has a certain degree of transparency when the thickness is 2 mm (see Figure 5 (b) in the figure), and further observed under a scanning electron microscope (SEM) that a microcrystalline glass with a 2-10 μm spot-like crystal morphology was successfully prepared (see Figure 8 ).

[0089] Under the excitation of 365 nm wavelength violet light, the transparent micro-ceramic glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured by Edinburgh FS980 fluorescence spectrometer. Fig. 9 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 532nm. The excitation spectrum covers a wide band of 250-450nm, and the excitation peak is at 365nm.

[0090] Fig.10 This is the temperature-varying spectrum diagram of the transparent microcrystalline glass of Example 2 at 300K-520K. It can be seen intuitively that the transparent microcrystalline glass still retains 70% of the initial luminous intensity at 423.15K, which further verifies that the transparent fluorescent microcrystalline glass of the present invention has good thermal stability.

[0091] Example 3

[0092] A transparent microcrystalline glass comprising α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Twin crystal phase.

[0093] A method for preparing transparent microcrystalline glass comprises the following steps:

[0094] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.6 mol% SrO, and 0.4 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0095] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 8 hours in the muffle furnace to obtain a block of α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Transparent glass-ceramics with twin crystal phases.

[0096] from Figure 4It can be seen from the X-ray diffraction peaks that α-Sr2SiO4:Eu 2+ and β-Sr2SiO4:Eu 2+ Twin crystal phase.

[0097] Under the excitation of 365 nm wavelength violet light, the transparent micro-ceramic glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured by Edinburgh FS980 fluorescence spectrometer. Fig.11 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 532nm. The excitation spectrum covers a wide band of 250-450nm, and the excitation peak is at 365nm.

[0098] Example 4

[0099] A transparent microcrystalline glass comprising β-Sr2SiO4:Eu 2+ Single crystal phase.

[0100] A method for preparing transparent microcrystalline glass comprises the following steps:

[0101] S1. Weigh the required raw materials SiO2, SrO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.3 mol% SrO, and 0.7 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;

[0102] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 8 hours in the muffle furnace to obtain a block of β-Sr2SiO4:Eu 2+ Transparent glass-ceramics in single crystal phase.

[0103] from Figure 4 It can be seen from the X-ray diffraction peaks that β-Sr2SiO4:Eu 2+ Single crystal phase.

[0104] The transparent glass-ceramics prepared in this embodiment still has a certain degree of transparency when the thickness is 2 mm (see Figure 5 (c)), and further observed under a scanning electron microscope (SEM) that a microcrystalline glass with a 2-10 μm spot-like crystal morphology was successfully prepared (see Fig.12 ).

[0105] Under the excitation of 365nm wavelength violet light, the transparent microcrystalline glass prepared in this example exhibits bright yellow-green luminescence. The normalized excitation and emission spectra at room temperature are measured using an Edinburgh FS980 fluorescence spectrometer. Fig.13 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 500nm. The excitation spectrum covers a wide band of 250-450nm, and the excitation peak is at 325nm.

[0106] A display device comprises the transparent microcrystalline glass of embodiment 1.

[0107] A lighting device comprises the transparent microcrystalline glass of embodiment 2.

[0108] On the basis of the above embodiments and within the scope of protection requested by the present invention, changes to the technical solutions of the present invention, such as changes in the dosage of the raw materials of the present invention, temperature and time, etc., which do not require creative labor, all fall within the scope of protection of the present invention.

Claims

1. A transparent glass-ceramic, It is characterized in that Including α-Sr 2 SiO 4 :Eu 2+ Single crystal phase transparent glass-ceramics, β-Sr 2 SiO 4 :Eu 2+ Single crystal phase transparent glass-ceramics, or α-Sr 2 SiO 4 :Eu 2+ and β-Sr 2 SiO 4 :Eu 2+ At least one of the twin crystal phases.

2. The transparent glass-ceramic according to claim 1, It is characterized in that The α-Sr 2 SiO 4 :Eu 2+ The single crystal phase has a spot-like crystal morphology; and / or, the β-Sr 2 SiO 4 :Eu 2+ The single crystal phase has a spot-like crystal morphology; and / or, the α-Sr 2 SiO 4 :Eu 2+ and β-Sr 2 SiO 4 :Eu 2+ The twin crystal phase has a spotty crystal morphology.

3. The transparent glass-ceramic according to claim 1, It is characterized in that The α-Sr 2 SiO 4 :Eu 2+ Single crystal phase transparent glass-ceramics, β-Sr 2 SiO 4 :Eu 2+ Single crystal phase transparent glass-ceramics, α-Sr 2 SiO 4 :Eu 2+ and β-Sr 2 SiO 4 :Eu 2+ The grain length of the twin crystal phase is 1-12 μm.

4. The transparent glass-ceramic according to claim 1, It is characterized in that The transparent microcrystalline glass can emit a broadband spectrum in the 400 to 700 nm band under 365 nm light excitation.

5. The transparent glass-ceramic according to claim 1, It is characterized in that The quantum efficiency of the transparent microcrystalline glass is not less than 74%.

6. The transparent glass-ceramic according to claim 1, It is characterized in that The transparent microcrystalline glass still retains more than 70% of the initial luminous intensity at 150°C.

7. A method for preparing the transparent microcrystalline glass according to any one of claims 1 to 6, It is characterized in that The following steps are involved: Weigh SiO 2 、SrO、Eu 2 O 3 The raw materials are then mixed, heated and melted in a reducing atmosphere, and then cooled to obtain the transparent microcrystalline glass; In the raw materials, the SiO 2 The molar percentage of SiO is 40-60%, the molar percentage of SrO is 40-60%, and the molar percentage of SrO is greater than that of SiO 2 The mole percentage of The heating and melting temperature exceeds 1510°C.

8. The preparation method according to claim 7, It is characterized in that In the raw material, the Eu 2 O 3 The molar percentage is 0.01-2%.

9. The preparation method according to claim 7, It is characterized in that The heating and melting temperature is 1570-1640°C, and the heating and melting temperature is kept at 1570-1640°C for 0.8-6 hours; and / or the reducing atmosphere is selected from H 2 , CO or carbon powder.

10. A display or lighting device, It is characterized in that Including the transparent microcrystalline glass as described in any one of claims 1-6.

Citation Information

Patent Citations

  • Microcrystalline glass for warm white LED and preparation method thereof

    CN106517797A

  • Fluorescent glass ceramic material, manufacture method thereof and illuminating device thereof

    CN108558213A

  • High-temperature-resistant high-expansion rare-earth-rich glass material as well as preparation method and application thereof

    CN114956576A

  • Purple light excitation glass ceramic for LED (light-emitting diode) illumination and preparation method of purple light excitation glass ceramic

    CN115716707A

  • Illuminating or light-receiving device and method for the production thereof

    WO2014009062A1